Amoebic chronic appendicitis: a rare entity - Krishna, M (Journal of Pathology of Nepal, 2016)
Rarely intestinal parasites can cause acute appendicitis. Amoebic appendicitis is rare and infection with Entamoeba Histolytica usually develops as an extension of caecal infection. I report a rare case of amoebic chronic appendicitis diagnosed on histopathology examination. It mimics the features of acute pappendicitis but may not always be responsible for acute appendicitis